Strain and strain rate in friction extrusion - Xiao Li; Md Reza-E-Rabby; Anthony Guzman; Glenn Grant; Suveen Mathaudhu; Micah Hinton; Anthony Reynolds (Journal of Materials Research and Technology, 2022)
Friction extrusion is a metal forming process that generates large plastic strains and deformation-induced heating through friction between a rotating die and the material to be extruded. The final deformation state in friction extruded wire has been visualized in previous studies but the distribution and evolution of strain and strain rate inside the solid material have yet to be elucidated. This paper develops an approach that reveals the deformation during the process by visualizing the shape change of the pre-embedded markers in the remnant billet. For the first time, the distribution of steady-state strain and strain rate in friction extrusion is determined via analysis of the shape changes of the deforming markers. The trend of strain and strain rate evolution from the undeformed zone to the extrusion die opening is revealed. The geometry of the deformation zone and “dead metal” zone are also deduced. This presented research provides an effective avenue for obtaining the necessary but previously unknown strain and strain rate values for establishing theoretical and numerical models for this thermomechanical process.